2022
DOI: 10.3390/biom12111699
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Two Trehalase Genes by RNA Interference Is Lethal to the White-Backed Planthopper Sogatella furcifera (Horváth) (Hemiptera: Delphacidae)

Abstract: Trehalase (Tre) is a crucial enzyme involved in trehalose metabolism, and it plays pivotal roles in insect development and metamorphosis. However, the biological function of Tre genes in Sogatella furcifera remains unclear. In the present study, two Tre genes—SfTre1 and SfTre2—were cloned and identified based on the S. furcifera transcriptome data. Bioinformatic analysis revealed that the full-length complementary DNA of SfTre1 and SfTre2 genes were 3700 and 2757 bp long, with 1728- and 1902-bp open reading fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In conjunction with findings from earlier research [58][59][60], we believe that trehalase inhibitors limit the energy availability of offspring by inhibiting trehalase or chitinase activity, or they are unable to break through the eggshell because of a lack of chitinase, thereby reducing the egg hatching rate. Experiments on the white-backed planthopper Sogatella furcifera [61] and cotton spider Tetranychus cinnabarinus [62] demonstrated a close correlation between chitinase activity and insect embryonic development, ovarian development, and egg hatching. A disruption of the trehalose pathway caused delayed ovarian development and egg formation in Bombyx mori [63].…”
Section: Discussionmentioning
confidence: 98%
“…In conjunction with findings from earlier research [58][59][60], we believe that trehalase inhibitors limit the energy availability of offspring by inhibiting trehalase or chitinase activity, or they are unable to break through the eggshell because of a lack of chitinase, thereby reducing the egg hatching rate. Experiments on the white-backed planthopper Sogatella furcifera [61] and cotton spider Tetranychus cinnabarinus [62] demonstrated a close correlation between chitinase activity and insect embryonic development, ovarian development, and egg hatching. A disruption of the trehalose pathway caused delayed ovarian development and egg formation in Bombyx mori [63].…”
Section: Discussionmentioning
confidence: 98%
“…The EtGFAT gene refers to the Glutamine: Fructose-6-Phosphate Aminotransferase gene of E. tenella [32], playing a crucial role in its metabolism. This gene encodes an enzyme involved in the gluconeogenesis pathway of glucose metabolism, converting glutamine and fructose-6-phosphate into glucosamine-6phosphate and glutamate [33]. In the lifecycle of E. tenella, the host animal's intestines provide ample glucose, which the enzyme encoded by the EtGFAT gene utilizes to support the parasite's growth and development [34].…”
Section: Discussionmentioning
confidence: 99%
“…Insect chitin remodeling is a highly complex process that is regulated by several enzymes. Previous studies have suggested that the suppression of specific insect chitin remodeling enzymes may be a useful strategy for developing pest control treatments [23,35,37,39]. GFAT is a crucial enzyme that catalyzes the rate-limiting step of the chitin biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [35], samples were collected during the feeding process. The sample collection schedule included 18 time points from the egg stage to the adult stage, including 1-2-day-old egg (EG1-EG2), 1-2-day-old 1st instar nymph (1L1-1L2), 1-2-dayold 2nd instar nymph (2L1-2L2), 1-3-day-old 3rd instar nymph (3L1-3L3), 1-3-day-old 4th instar nymph (4L1-4L3), 1-3-day-old 5th instar nymph (5L1-5L3), and 1-3-day-old adult (AD1-AD3).…”
Section: Insect Rearing and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation